Peran Kesejahteraan di Tempat Kerja terhadap Keinginan untuk Tetap bertahan pada Milenial - Luthfiana, Nusaiba; Zamralita, Zamralita; Idulfilastri, Rita Markus (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This research investigates the role of workplace well-being on Millennials'  intention to stay. Intention to stay refers to a person's tendency to stay in the organization where they work for a more extended period. Workplace well-being is a sense of well-being obtained from work related to the feelings of workers in general (core affect) and intrinsic and extrinsic work values. A cross-sectional survey design was used in this study. Data was collected through a Google form distributed to employees in the Jabodetabek area aged 27-40 with a minimum of 1 year of working experience, and the last education was high school or equivalent—the completed questionnaire obtained 211 answers. The instrument for measuring the will to survive uses the Intention to Stay Scale adaptation scale from Kyndt et al. (2009), and well-being at work is measured by the Work Well-Being Questionnaire from Parker and Hyett (2014). The statistical analysis used was descriptive statistics, Spearman correlation statistics, Confirmatory Factor Analysis (CFA), and exponential regression. There is a positive and significant role of workplace well-being on intention to stay in Millennials with an R square of 0.821, and the regression equation is Y = 1.431 + 0.255 X. Research has shown that when employees feel cared for, valued, and supported at work, they tend to have higher intentions to stay employed.